Dividend Policy: A Survey of Malaysian Public Listed Companies and Security Analysts - Chong, David Voon Chee (2003)
This dissertation revisits the dividend puzzle and attempts to answer the fundamental question of “why do companies pay dividends?” by using a simple regression model incorporating the major theories on dividend relevance. In addition, this research investigates if the opinions of companies (both dividend and non-dividend paying) and security analysts differ with respect to the various explanations for paying dividends. Finally, this research also explores the views and opinions of corporate managers with respect to the dividend setting process and to a relatively new corporate practice in Malaysia, that is, share repurchases. Data is obtained from a mail survey sent to chief financial officers of companies listed on the Kuala Lumpur Stock Exchange. The results indicate that the taxation and dividend clientele theories best explains the reason for dividend relevance, but this only explains 32.2% of the variation. Hence, a large portion of the variance remains unaccounted for and may be due to other anomalies or market frictions which have not been taken into account in this model. In terms of the opinions and views of dividend paying companies, non-dividend paying companies and security analysts, generally, all three groups appear to hold similar views with regards to the various theories except for the agency cost theory, where concerns of mismanagement of excess funds appear more pronounced for security analysts than corporate managers. Based on the opinions obtained for the various individual statements explaining dividend relevance, the explanation most favoured by managers appears to be the bird-in-hand theory and some insight as to why this explanation is favoured was provided by some of the respondents. The agency, signalling and taxation/dividend clientele theories, on overall, received mixed responses. With respect to the dividend setting process, the findings obtained are remarkably similar with that of Lintner (1956) while for share repurchases, corporate managers appear to agree with the signalling theory as a reason for repurchasing shares.